Embedded systems architecture a comprehensive guide for engineers and programmers - Noergaard, Tammy (Elsevier/Newnes, 2005)
This comprehensive textbook provides a broad and in-depth overview of embedded systems architecture for engineering students and embedded systems professionals. The book is well suited for undergraduate embedded systems courses in electronics/electrical engineering and engineering technology (EET) departments in universities and colleges, as well as for corporate training of employees. The book is a readable and practical guide covering embedded hardware, firmware, and applications. It clarifies all concepts with references to current embedded technology as it exists in the industry today, including many diagrams and applicable computer code. Among the topics covered in detail are: hardware components, including processors, memory, buses, and I/O system software, including device drivers and operating systems use of assembly language and high-level languages such as C and Java interfacing and networking case studies of real-world embedded designs applicable standards grouped by system application The CD-ROM accompanying the text contains source code for the design examples and numerous design tools useful to both students and professionals. A detailed laboratory manual suitable for a lab course in embedded systems design is also provided. Ancillaries also include a solutions manual and technical slides. * Without a doubt the most accessible, comprehensive yet comprehensible book on embedded systems ever written! * Leading companies and universities have been involved in the development of the content * An instant classic!
Keywords: Embedded computer systems.; Computer architecture.; elektronické knihy; electronic books